The RB621 antibody recognizes the envelope E protein from SARS-CoV-2 by immunofluorescence - Marchetti, Anna; Zenhausern, Frederic (Antibody Reports, 2020)
The recombinant antibody RB621 detects by immunofluorescence the envelope E protein from SARS-CoV-2.